2019
DOI: 10.1007/s10930-019-09868-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis on Fruit Ripening Processes in Two Varieties of Tropical Mango (Mangifera indica)

Abstract: Check the metadata sheet to make sure that the header information, especially author names and the corresponding affiliations are correctly shown. • Check the questions that may have arisen during copy editing and insert your answers/ corrections. • Check that the text is complete and that all figures, tables and their legends are included. Also check the accuracy of special characters, equations, and electronic supplementary material if applicable. If necessary refer to the Edited manuscript. • The publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
0
9
0
1
Order By: Relevance
“…4’ mangoes had a green to pale green color over the same period, although the pulp color was altered. Chin et al indicated that the color of ‘Chokanan’ mango cultivars changed from green to yellow within 0–8 days of ripening [ 8 ]. The degradation of pectin and the carbohydrate breakdown process occur during ripening.…”
Section: Resultsmentioning
confidence: 99%
“…4’ mangoes had a green to pale green color over the same period, although the pulp color was altered. Chin et al indicated that the color of ‘Chokanan’ mango cultivars changed from green to yellow within 0–8 days of ripening [ 8 ]. The degradation of pectin and the carbohydrate breakdown process occur during ripening.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress can cause the accumulation of ROS, and by causing cellular membrane damage; the excess ROS participate in the process of fruit ripening [71,72]. According to Chin et al [73], control of oxidative stress in mango fruits can extend the shelf life in the postharvest stage. Thus, these results demonstrate that oxidative stress regulates fruit ripening by regulating ROS metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The most noticeable changes during ripening were alterations in the external color from green to yellow, which occurred from day 0 to day 8 of ripening. As described by Chin et al [12], "Chokanan" mango cultivar has changed the color from green to yellow within day 8 of the ripening period at 25 ± 1 °C. However, Lalel et al [13] reported that mango ripening occurred within day 9 to day 12 postharvest at an ambient temperature (21 ± 1 °C).…”
Section: Ripening Appearance Of Nam Dok Mai Si Thong Mangomentioning
confidence: 90%